Empirical examination of relationship between venture capital financing and profitability of portfolio companies in Uganda - Ahmed I. Kato; Chiloane-Phetla E. Germinah (Journal of Innovation and Entrepreneurship, 2022)
In recent times, venture capital (VC) financing has evolved as an alternative feasible funding model for young innovative companies. Existing studies focus on whether VC enhances profitability. While helpful, this body of work does not address a critical question: whether VC firms are more profitable than non-VC firms. The co-existence of both VC and non VC firms in Africa provides an opportunity to address this question. Accordingly, this paper sought to extend the understanding of the relationship between VC financing and the profitability of portfolio companies in Uganda, a rapidly growing VC market. We utilised a mixed methods approach, which involved quantitative data collected from 68 key VC stakeholders, and qualitative data collected from 16 semi-structured face-to-face interviews. The results confirm the superior performance of VC-financed enterprises when compared to non-VC-financed enterprises. The study makes a vital contribution by offering a diversified framework for enterprise success. The framework will assist VC firms in evaluating and customising funding programmes that can propel early-stage firms' success in Uganda, and in similar emerging economies. Secondly, our results contribute to extant knowledge about recent developments in Uganda's VC industry and how it influences the profitability trends of SMEs, also in similar emerging economies.
Keywords: G2; G24; L26; 650; Diversified-framework for enterprise success; Profitability and small and medium enterprises; Uganda; Venture capital